Perbandingan Persepsi Pemilik Jenama terhadap Desain Identitas Visual hasil Generative AI dan Desainer Manusia - Mutiara Chandra Nursobrina; Rahina Nugrahani; Muhammad Ariffudin Islam (Lembaga Pengembangan Kinerja Dosen, 2026)
Generative Artificial Intelligence (AI) has revolutionized visual design, yet its capability in creating brand identities remains questioned. This study analyzes brand owners' perceptions of logo designs produced by generative AI versus human designers based on an identical design brief. Employing a qualitative approach with a controlled experimental design, this research involved the owner of Cataleya Kitchen, a gluten-free culinary MSME in Semarang, Indonesia. Blind evaluation and post-disclosure reflection sessions were used to assess four logo stimuli: two created by a professional designer and two generated via AI prompting on Adobe Firefly. Data were evaluated using thematic analysis across five dimensions: simplicity, legibility, clarity, brand fit, and memorability. The results indicated that human-designed logos achieved superior ratings in all dimensions, driven by the designer's grasp of color semantics, composition, and emotional resonance. Conversely, generative AI showed significant limitations in cultural contextual understanding, particularly regarding Indonesian culinary culture. This study concludes that the Human-in-the-Loop (HITL) approach offers the optimal strategy for MSMEs seeking authentic visual identities despite resource constraints.